Pengelolaan Pembelajaran Biologi Berbasis LingkunganDi MTs Negeri I Sragen - Sriyono, Prof.Dr.Sutama ,M.Pd (2016)
Sriyono. Q100110059, biology-based learning management environment at MTs Negeri 1 Sragen. Thesis. Post graduate programs Universitas Muhammadiyah Surakarta 2016 the general purpose of this study to describe the processing of biological-based learning environment in MTs Negeri 1 Sragen, while the special purpose of this study to describe the biology Planning based learning environment at MTs Negeri 1 Sragen. Implementation of biology-based learning environment at MTs Negeri 1 Sragen. Evaluation of biology-based learning environment at MTs Negeri 1 Sragen. Type of research is qualitative, the main subject of this research is the principal, vice principal affairs curriculum, teachers, learners, while the collection of data using in-depth interviews, observation and documentation. Data analysis begins with data collection, data reduction, data display and conclusion. the validity of test data by using the credibility and triangulation. The results of this study are. Planning the learning begins with the development of the syllabus which are translated at the RPP, the program comes with an annual, semi-annual programs, which are arranged in groups KKM, KKG. The implementation of learning through three phases: initial, core stage, the final stage which is supported by the management of learning spaces, the selection of appropriate materials, the use of interesting and exciting media. Evaluation of learning done with the process and the results, while the follow-up in the form of remedial and enrichment keywords: planning, implementation, evaluation